Implementation of a Pilot Study to Analyze Circulating Tumor DNA in Early-Stage Lung Cancer - Macedo, Joana Espiga de Macedo (2023)
Introduction: Liquid biopsies based on plasma circulating tumour deoxyribonucleic acid (ctDNA) have shown promise in monitoring lung cancer evolution. The expression of ctDNA across time, its relationship with clinicopathological parameters and its association with lung cancer progression through imaging allow us to weigh how useful ctDNA could be in monitoring surgically resectable lung cancer. The aim of this study was to assess the impact of ctDNA analysis implementation in early-stage lung cancer.Methods: A cohort of 47 patients was sequentially recruited. Only 34 patients with early-stage lung cancer were included. All patients had a tissue specimen and five blood samples drawn: at the preoperative stage, from the pulmonary vein, at surgical discharge, at the first follow-up and at the last follow-up. All blood samples were evaluated for ctDNA expression. Results: On average, the maximum yield of ctDNA was obtained in liquid biopsies at the surgical discharge of patients when compared with PO, PV, and F1 (p < 0.0001, p < 0.0001, p < 0.0001 respectively). No statistically significant differences were found when comparing the last follow-up to surgical discharge ctDNA expression (p = 0.851). The correlation between ctDNA concentration according to five-time points and the four clinicopathological characteristics showed that patients younger than 70 years had a statistically significant reduction of the concentration of ctDNA at the preoperative and surgical discharge time point [β = -16 734 (-27 707; - 5760); p = 0.003; β = -21 785 (-38 447; -5123); p = 0.010], as opposed to an increase of the concentration of ctDNA at the pulmonary vein and last follow-up time points [β = 8369 (0.359; 16 378); p = 0.041; β = 34 402 (12 549; 56 254); p = 0.002] all with a confidence level of 95%. In the cases where actionable mutations were identified in tissue biopsies, the expected mutation was found in five out of six patients plasma samples at the pre-operatory time point and in two out of six patients plasma samples at the pulmonary vein time point. Two out of six patients with actionable mutations had disease progression.Conclusion: The results of this pilot study suggest that the maximum yield of ctDNA is obtained at the surgical discharge of the patients and that the pre-operatory timepoint is the one offering the highest sensitivity for the detection of actionable mutations in ctDNA in early-stage lung cancer.